The Effect of The Use of Debit Cards and Electronic Money (E-Money) on Public Consumption Expenditures in Pematangsiantar City - Sipayung, Tuahman; Sriwijayanti, Eva; Munthe, Risma; Okto Posmaida Damanik, Elvina (KnE Social Sciences, 2023)
This study aims to determine the effect of the use of debit cards and electronic money (e-money) on public consumption expenditure of Pematangsiantar City. The population in this study are Pematangsiantar City people who have debit cards and electronic money (e-money). The sampling technique used in this study was purposive sampling technique. The number of samples is 100 respondents. This study uses primary data obtained from a questionnaire and then analyzed by multiple linear regression. Based on the results of the t test (partial), there is a significant influence between the use of a debit card on the consumption expenditure of Pematangsiantar City. Furthermore, the use of electronic money (e-money) has a significant effect on the consumption expenditure of the Pematangsiantar City community. Based on the test results of the coefficient of determination (Adj R2), the value was 0.638 (63.8%). This shows that the variations in consumption expenditure of Pematangsiantar City can be explained by debit cards and electronic money. While the remaining 36.2% is explained by other factors not included in this study. This is because non-cash payments are easy to use and psychologically, it is easier for anyone to spend their money in cash than in cash. The results of this study indicate that the people of Pematangsiantar City are consumptive, especially those under 40 years of age. There is a need for increased socialization regarding non-cash transactions, because it cannot be denied that in the Pematangsiantar City area there are still some people who do not quite understand non-cash transactions, especially those aged 40 years and over. Keywords: e-Money; debit cards; public consumption